Analysis of consumption of S01E groups of drugs - antiglaucoma drugs and miotics - А. А. Kotvitska; О. А. Pastukhova (Zaporozhye State Medical University, 2014)
Aim. The question of health protection and promotion for elderly population is very acute in modern conditions of global demographic population aging. Paying attention to the significant increase in glaucoma morbidity among this population contingent, the results of research consumption of drugs used to treat glaucoma in the period 2009-2012 are presented in the article. Methods and results. Sales volumes of antiglaucoma preparations and miotics have been established in monetary and physical terms. These drugs groups' consumption of domestic and foreign production has been analyzed. The dynamics of each group's consumption of products of specified segment has been investigated.